2020
DOI: 10.31729/jnma.5296
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Thyroid Dysfunction Among Depression Patients in a Tertiary Care Centre

Abstract: Introduction: Patients with thyroid disorders are more prone to develop depressive symptoms and conversely depression may be accompanied by various subtle thyroid abnormalities. The aim of the study was to estimate the prevalence of thyroid dysfunction in depression. Methods: This is a descriptive cross-sectional study conducted at Devdaha Medical College and Research Institute employing a simple random sampling technique during the period of August 2019-January 2020. The research was approved by the Eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…6 In another study by Chawanun Charnsil and Sutrak Pilakanta et al, subclinical hyperthyroidism and the remaining 4.3% Some studies have reported a higher prevalence of thyroid dysfunction (26%) than the present study. 13 Another important finding of this study was that there was no significant association between the severity of depressive symptoms and characteristic thyroid dysfunction, which is similar to the findings of Charnsil et al 2 However, this finding is in contrast with a study by Ojha et al, who reported significant correlation that is, more severe the depression higher is the prevalence of thyroid dysfunction. 6 Possible explanations could be differences in diagnostic criteria used for diagnosis and differences in severity of depressive episodes included in both the studies.…”
Section: Discussionsupporting
confidence: 82%
“…6 In another study by Chawanun Charnsil and Sutrak Pilakanta et al, subclinical hyperthyroidism and the remaining 4.3% Some studies have reported a higher prevalence of thyroid dysfunction (26%) than the present study. 13 Another important finding of this study was that there was no significant association between the severity of depressive symptoms and characteristic thyroid dysfunction, which is similar to the findings of Charnsil et al 2 However, this finding is in contrast with a study by Ojha et al, who reported significant correlation that is, more severe the depression higher is the prevalence of thyroid dysfunction. 6 Possible explanations could be differences in diagnostic criteria used for diagnosis and differences in severity of depressive episodes included in both the studies.…”
Section: Discussionsupporting
confidence: 82%
“…Thyroid dysfunction is associated with the occurrence of various neuropsychiatric disorders, including depression (Kafle et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, healthcare providers are likely to spend more time on consultation and suggest more examinations for patients with multiple chronic conditions. Third, healthcare providers often prescribe thyroid function and blook lipid tests for patients with mental health disorders, because they all believe thyroid function is strongly associated with emotional problems and patients with thyroid imbalance are more likely to develop lipid problems 34 . Fourth, for patients with long-term treatment of psychotropic drugs, healthcare providers often suggest them to do liver and kidney function tests regularly, because long-term use of medication may cause liver or kidney function damage 35 .…”
Section: Discussionmentioning
confidence: 99%